Clitoral Vascularization and Sexual Behavior in Young Patients Treated with Drospirenone–Ethinyl Estradiol or Contraceptive Vaginal Ring: A Prospective, Randomized, Pilot Study. (2nd December 2013) - Battaglia, Cesare; Morotti, Elena; Persico, Nicola; Battaglia, Bruno; Busacchi, Paolo; Casadio, Paolo; Paradisi, Roberto; Venturoli, Stefano
Abstract Introduction Oral contraceptives (OC) are effective for birth control and have good cycle control and tolerability. However, the hormonal components could modify mood and libido. Aim The aim of this study is to evaluate the genital vascular effects and sexual behavior of an OC containing 30 μg ethinyl estradiol and 3 mg drospirenone in comparison with a flexible combined contraceptive vaginal ring. Methods Forty women underwent a sonographic assessment of the clitoral anatomy and vascularization and were administered the McCoy Female Sexuality Questionnaire (MFSQ) and the Beck's Depression Inventory questionnaire (BDI). Estradiol, androstenedione, testosterone, and SHBG were assayed. Free Androgen Index (FAI) and Free Estrogen Index (FEI) were calculated. The patients were randomly submitted to OC (group I; n = 21) or vaginal ring (group II; n = 19). Main Outcome Measures Ultrasonographic clitoral volume, pulsatility index (PI) of dorsal clitoral arteries, MFSQ, BDI, and hormonal and biochemical assays were analyzed. Results After therapy, the testosterone levels were reduced in both groups, whereas estradiol decreased only in group I women. The SHBG increased in all the subjects, and both FAI and FEI decreased. The clitoral volume decreased in all the women. The PI of the dorsal clitoral artery increased only in patients on OC. The hormonal contraception was associated, in both studied groups, with a significant decrease of the two‐factor Italian MFSQ score, which was more marked in OC users. In group I subjects, there was a reduction of the number of intercourse/week and a reduction of orgasm frequency during intercourse. The pain during intercourse worsened after OC use. The vaginal ring users reported a vaginal wetness. Conclusions Six‐month treatment with hormonal contraception is associated with a diminished MFSQ score. However, the frequency of sexual intercourse and orgasm was reduced only by the use of OC. The OC use was associated with increased pain during intercourse. Battaglia C, Morotti E, Persico N, Battaglia B, Busacchi P, Casadio P, Paradisi R, and Venturoli S. Clitoral vascularization and sexual behavior in young patients treated with drospirenone–ethinyl estradiol or contraceptive vaginal ring: A prospective, randomized, pilot study. J Sex Med 2014;11:471–480.